Psychological Well Being Ibu yang Memiliki Anak berkebutuhan Khusus : Peran Dukungan Sosial - Karima, Annisa Alfi; Winta, Mulya Virgonita Iswindari; Amelia, Cristine Roselvia Tri Amelia (Universitas Semarang, 2023)
This study aims to determine the relationship between social support and psychological well-being in mothers who have children with special needs at the Klinik Tumbuh Kembang Yamet CDC Semarang. The hypothesis proposed in this study is that there is a positive relationship between social support and psychological well-being in mothers who have children with special needs at the Klinik Tumbuh Kembang Yamet CDC Semarang. The higher the social support, the higher the psychological well-being for 41 mothers who have children with special needs at the Klinik Tumbuh Kembang Yamet CDC Semarang, and vice versa. The respondents in this study were mothers who had children with special needs who were being treated at the Semarang Growth and Development Clinic. The sampling technique used is a saturated sampling technique (simple sampling). The research data was collected using two scales, namely the Psychological Well-Being Dimension in Mothers Who Have Children with Special Needs and the Social Support Scale. Data analysis was carried out using the Product Moment Correlation technique. The results showed that there was a negative relationship between social support and psychological well-being in mothers who had children with special needs with rxy values = -0.507, p = 0.001 (p< 0.01), so the hypothesis in this study was rejected